Optimization parameter design of a circular e＋e- Higgs factory - 王逗 高杰 肖铭 耿会平 郭媛媛 许守彦 王娜 安宇文 秦庆 徐刚 王生 (Chinese physics C, 2013)
In this paper we will show a general method of how to make an optimized parameter design of a circular e＋e- Higgs factory by using analytical expression of maximum beam-beam parameter and beamstrahlung beam lifetime starting from a given design goal and technical limitations. A parameter space has been explored. Based on beam parameters scan and RF parameters scan, a set of optimized parameter designs for 50 km Circular Higgs Factory （CHF） with different RF frequency was proposed.